Preparation method of high-purity ammonium rhenate
High-purity ammonium perrylate was extracted from rhenium-rich slag in copper smelting systems by high-pressure autoclave leaching, four-stage anion exchange, and micro-pressure ultrasonic crystallization. This method solved the problems of uneven purification and impurity introduction in existing ammonium perrylate technologies, and achieved the preparation of high-purity and high-crystallinity ammonium perrylate.
Patent Information
- Application Number
- CN202511827598.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-05
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies for purifying ammonium perrylate include precipitation methods which consume a lot of chemical reagents and produce uneven products, extraction methods which are volatile and toxic and introduce impurities, and ion exchange methods which produce products with a high concentration of perrylate ions, making it difficult to achieve high purity.
Ammonium perryate was extracted from rhenium-rich slag in a copper smelting system by a method of high-pressure autoclave heating and stirring leaching, four-stage anion exchange column purification, and micro-pressure ultrasonic crystallization. High-purity ammonium perryate crystals were formed by controlling the stirring rate, pressure, temperature, and ultrasonic power.
This improved the purity and crystallization rate of ammonium perrylate, simplified the process, and enhanced the product's activity and application value.
Smart Images

Figure CN121377124A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ammonium perrylate preparation technology, specifically a method for preparing high-purity ammonium perrylate. Background Technology
[0002] The purity of ammonium perrylate plays a decisive role in the purity of rhenium products, while the purity of metallic rhenium affects its application performance; poor purity will impair rhenium's application in high-temperature and high-vacuum environments. Therefore, purifying ammonium perrylate to prepare high-purity ammonium perrylate is crucial. Currently, the main methods for purifying ammonium perrylate include precipitation, extraction, and ion exchange processes. Precipitation consumes high levels of chemical reagents, produces precipitates with uneven particle size and shape, and is not conducive to obtaining high-purity products. Extraction is simple and easy to operate, but the organic matter is volatile and toxic, and it easily introduces unnecessary impurity ions. Currently, most ion exchange methods use cation exchange, concentration, cooling, and crystallization, which easily results in a large number of perrylate ions in the product, making it impossible to achieve high purity. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing high-purity ammonium perrylate, which extracts rhenium from rhenium-rich slag produced by copper smelting system and purifies it to produce highly active and pure ammonium perrylate crystals, thereby improving the comprehensive utilization rate of copper smelting slag and shortening the process.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing high-purity ammonium perrylate includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir evenly. The solid-liquid ratio of rhenium-rich slag and water is 1:3-5. Add hydrogen peroxide as an oxidant. Heat to 80-90℃ while stirring at a rate of 150-200 r / min. Pressurize to 0.6-1.0 MPa with air and leach for 60-90 minutes. Filter precisely and let stand to obtain the leachate. Step 2: Pass the leachate prepared in Step 1 through a four-stage anion exchange column. When the rhenium content in the solution after adsorption at the fourth stage anion exchange column is detected to be 0.1-0.5 mg / L, confirm that the resin in the first-stage ion exchange column is saturated, stop the ion exchange, and then elute the first-stage exchange column with high-quality ammonia. During the elution process, rhenium ions enter the ammonia to form an ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia... - The radical ions then bind with the resin, purifying the concentrated ammonium perrylate solution to a rhenium concentration of 15-20 g / L. Step 3: Inject the purified and enriched ammonium perrylate solution prepared in Step 2 into an evaporation container. Under the action of micro-pressure ultrasound, perform high-temperature thermal crystallization by heating and evaporation. The stirring speed is 150-200 r / min, the pressure is 0.2 kPa, the ultrasonic power is 3000-5000 W, and the heating temperature is above 95℃. Under these conditions, when a large number of crystals appear in the solution, stop heating when the specific gravity of the solution reaches 1.1-1.15. Stop stirring and turn off the ultrasonic generator when the solution temperature drops below 30℃. Centrifuge and dry the crystals to obtain high-purity ammonium perrylate crystals with a purity ≥4N.
[0005] Preferably, the mass percentage content of the main components in the rhenium-rich slag is as follows: rhenium 1-2%, copper 5-8%, bismuth 1-3%, arsenic 0.5-1%, sulfur 30.0-34.2%, oxygen 21-25.8%, and sodium 3-5%.
[0006] Preferably, the main components of the leachate produced in step one are: rhenium 2-5 g / L, acidity 50-80%, copper 15-20 g / L, bismuth 3-7 g / L, arsenic 0.5-1.0 g / L, sodium 10-13 g / L, and sulfur 20-25 g / L.
[0007] Preferably, the filter paper used for precision filtration in step one has a pore size of 1-5 micrometers.
[0008] Preferably, in step two, the leachate is sequentially passed through a four-stage anion exchange column at a flow rate of 80-100 mL / min. After passing through the four-stage anion exchange column, the perylene ions are adsorbed by the exchange resin, and the OH groups on the resin are... - Released into the solution and reacting with H - The ions combine to form H2O, which is discharged with the adsorbed liquid. The adsorbed liquid then enters the copper smelting system to recover copper and other valuable metals.
[0009] Preferably, the ion exchange column is filled with a weakly basic macroporous anion exchange resin with a tertiary amine functional group, named RCX-5, and the amount of ion exchange resin is 2 / 3 of the column volume.
[0010] Preferably, the amount of hydrogen peroxide used in step one is 1.2-1.5 times the theoretical amount.
[0011] Preferably, in step two, the superior ammonia water is chemically pure ammonia water with a mass percentage concentration of 5-10%, and the flow rate of the ammonia water is 30-50 ml / min when the saturated anion exchange column is desorbed.
[0012] Preferably, the drying conditions for the crystals in step three are: drying at 150°C for 24 hours.
[0013] In step one of this invention, rhenium disulfide in the rhenium-rich slag is oxidized under high pressure to form rhenium acid, and low-valence rhenium is converted into high-valence rhenium, which enters the solution. The high pressure increases the oxidation effect of hydrogen peroxide, thereby improving the leaching rate of rhenium. The leaching process causes the rhenium disulfide in the rhenium-rich slag to react chemically with hydrogen peroxide under high temperature and high pressure to generate soluble perrhenium acid, which can make the leaching rate of rhenium greater than 98%.
[0014] The reaction principle is as follows: ReS2 + 4H2O2 → H2ReO4 + H2O + 2S 2H₂O₂ + S → 2H₂O + SO₂ 3H₂O₂ + S → 2H₂O + H₂SO₄ In step two of this invention, the anion exchange column uses a macroporous weakly basic anion exchange resin with a tertiary amine functional group, named RCX-5. The amount of exchange resin packed is 2 / 3 of the column volume, which can improve the adsorption of anions such as sulfuric acid and arsenic acid.
[0015] In step two of this invention, when the ammonium peroxide solution formed by using high-grade ammonia as the eluent crystallizes, excess ammonia gas is easily volatilized and does not easily remain in the crystal. If sodium hydroxide is used as the eluent, sodium ions are more likely to remain in the crystal, affecting the purity of the ammonium peroxide.
[0016] In step three of this invention, the micro-pressure accelerates the evaporation rate, and the high-temperature thermal crystallization under the action of ultrasound improves the activity of ions, resulting in finer and more uniform crystal particles with stronger activity and higher crystallization rate. In addition, it reduces the adhesion of impurity ions during crystal formation.
[0017] The method described in this invention has a simple process, and the prepared product has strong activity, high crystallinity, and excellent purity, and has high application value. Attached Figure Description
[0018] Figure 1 It is the high-purity ammonium perrylate powder prepared in Example 1 after drying; Figure 2 It is the undried high-purity ammonium perrylate powder prepared in Example 1; Figure 3 This is a mirror image of the high-purity ammonium perrylate powder prepared in Example 1. Detailed Implementation
[0019] The present invention will be further described in detail below with reference to specific embodiments.
[0020] Example 1 A method for preparing high-purity ammonium rheniumate, wherein the main components in the rhenium-rich slag have the following contents: rhenium 1.7%, copper 5.2%, bismuth 1.4%, arsenic 0.5%, sulfur 33.9%, oxygen 21.9%, and sodium 3.2%; the method includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir until homogeneous. The solid-liquid ratio of rhenium-rich slag to water is 1:4. Add hydrogen peroxide, with the amount of hydrogen peroxide being 1.2 times the theoretical amount. Heat to 80°C while stirring at 200 r / min, and pressurize to 0.6 MPa with air. Leach for 60 min, then filter precisely and allow to stand to obtain the leachate. The filter paper pore size is 5 micrometers. The main components of the leachate are: rhenium 3.94 g / L, acidity 60%, copper 15.2 g / L, bismuth 4.5 g / L, arsenic 0.5 g / L, and sodium 8.6 g / L. Step 2: The leachate prepared in Step 1 is sequentially injected into a four-stage anion exchange column. The leachate passes through the four-stage anion exchange column sequentially at an ion exchange flow rate of 80 mL / min. After passing through the four-stage anion exchange column, the rhenium ions are adsorbed onto the exchange resin, and the OH groups on the resin... - Released into the solution and reacting with H - Ions combine to form H₂O, which is discharged with the adsorption liquid. The adsorption liquid then enters the copper smelting system to recover copper and other valuable metals. When the rhenium content in the adsorption liquid of the fourth-stage anion exchange column is detected to be 0.3 mg / L, it is confirmed that the resin of the first-stage ion exchange column is saturated. Ion exchange is stopped, and the first-stage exchange column is eluented with 5% (w / w) high-grade ammonia at a flow rate of 30 ml / min. During the eluenting process, rhenium ions enter the ammonia water to form ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia water... - The radical ions bind to the resin, and the concentration of rhenium in the ammonium perrylate solution is 20 g / L; Step 3: Inject the purified and enriched ammonium perryate solution prepared in Step 2 into an evaporation container. Under the action of micro-pressure ultrasound, heat evaporation and high-temperature thermal crystallization are carried out. The stirring speed is 150 r / min, the pressure is 0.2 kPa, the ultrasonic power is 3000 W, and the heating temperature is above 95℃. When a large number of crystals appear, the heating is stopped when the specific gravity of the solution reaches 1.15. When the solution temperature drops below 30℃, stirring is stopped and the ultrasonic generator is turned off. The crystals are separated by centrifugation and dried at 150℃ for 24 h to obtain high-purity ammonium perryate with a purity ≥4N.
[0021] The mass percentage content of each major component in the prepared product, as tested, is as follows: ammonium perrylate 99.9965%, other impurities arsenic 0.0002%, copper 0.001%, sodium 0.0001%, zinc 0.0001%, and iron 0.001%.
[0022] The high-purity ammonium perrye prepared in this embodiment is as follows: Figures 1 to 3 As shown.
[0023] Example 2 A method for preparing high-purity ammonium rheniumate, wherein the main components in the rhenium-rich slag are: rhenium 1.9%, copper 5.6%, bismuth 1.2%, arsenic 0.6%, sulfur 32.4%, oxygen 22.3%, and sodium 4.1%; the method includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir evenly. The solid-liquid ratio of rhenium-rich slag to water is 1:5. Add hydrogen peroxide, with the amount of hydrogen peroxide being 1.5 times the theoretical amount. Heat to 90°C while stirring at 200 r / min, pressurize to 1.0 MPa with air, and leach for 90 min. Filter precisely and allow to stand to obtain the leachate. The filter paper pore size is 1 micrometer. The main components of the leachate are: rhenium 3.50 g / L, acidity 50%, copper 25.2 g / L, bismuth 3.8 g / L, arsenic 1.0 g / L, sodium 12.6 g / L, and sulfur 22.5 g / L. Step 2: Inject the leachate prepared in Step 1 into a four-stage anion exchange column. The leachate passes through the four-stage anion exchange column sequentially at a flow rate of 100 mL / min. After passing through the four-stage anion exchange column, the rhenium ions are adsorbed onto the exchange resin, and the OH groups on the resin... - Released into the solution and reacting with H - Ions combine to form H₂O, which is discharged with the adsorption liquid. The adsorption liquid then enters the copper smelting system to recover copper and other valuable metals. When the rhenium content in the adsorption liquid of the fourth-stage anion exchange column is detected to be 0.3 mg / L, it is confirmed that the resin of the first-stage ion exchange column is saturated. Ion exchange is stopped, and the first-stage exchange column is eluented with 10% (w / w) high-grade ammonia at a flow rate of 50 ml / min. During the eluenting process, rhenium ions enter the ammonia water to form ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia water... - The radical ions bind to the resin, and the concentration of rhenium in the ammonium perrylate solution is 20 g / L; Step 3: Inject the purified and enriched ammonium perryate solution prepared in Step 2 into an evaporation container. Under the action of micro-pressure ultrasound, perform heating and evaporation thermal crystallization. The stirring speed is 200 r / min, the pressure is 0.2 kPa, the ultrasonic power is 5000 W, and the heating temperature is above 95℃. When a large number of crystals appear, stop heating when the specific gravity of the solution reaches 1.15. Stop stirring and turn off the ultrasonic generator when the solution temperature drops below 30℃. Centrifuge the crystals and dry them at 150℃ for 24 h to obtain high-purity ammonium perryate with a purity ≥4N.
[0024] The content of the main components in the prepared product was tested and found to be: ammonium perrylate 99.996%, other impurities arsenic 0.00001%, copper 0.001%, sodium 0.0001%, zinc 0.0001%, and iron 0.0005%.
[0025] Example 3 A method for preparing high-purity ammonium rheniumate, wherein the main components of the rhenium-rich slag are: rhenium 2.0%, copper 6.3%, bismuth 1.2%, arsenic 0.67%, sulfur 31.2%, oxygen 23.0%, and sodium 4.5%; the method includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir evenly. The solid-liquid ratio of rhenium-rich slag to water is 1:3. Add hydrogen peroxide as an oxidant, with the amount of hydrogen peroxide being 1.4 times the theoretical amount. Heat to 85°C while stirring at 180 r / min, pressurize to 0.8 MPa with air, and leach for 70 min. Filter precisely and allow to stand to obtain the leachate. The filter paper pore size is 4 micrometers. The main components of the leachate are: rhenium 4.83 g / L, acidity 80%, copper 18.1 g / L, bismuth 7.6 g / L, arsenic 0.37 g / L, sodium 12.5 g / L, and sulfur 25.8 g / L. Step 2: Inject the leachate prepared in Step 1 into a four-stage anion exchange column. The leachate passes through the four-stage anion exchange column sequentially at a flow rate of 90 mL / min. After passing through the four-stage anion exchange column, the rhenium ions are adsorbed onto the exchange resin, and the OH groups on the resin... - Released into the solution and reacting with H - Ions combine to form H₂O, which is discharged with the adsorption liquid. The adsorption liquid then enters the copper smelting system to recover copper and other valuable metals. When the rhenium content in the adsorption liquid of the fourth-stage anion exchange column is detected to be 0.4 mg / L, it is confirmed that the resin of the first-stage ion exchange column is saturated. Ion exchange is stopped, and the first-stage exchange column is eluented with 8% (w / w) high-grade ammonia at a flow rate of 35 ml / min. During the eluenting process, rhenium ions enter the ammonia water to form ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia water... - The radical ions bind to the resin, and the concentration of rhenium in the ammonium perrylate solution is 15 g / L; Step 3: Inject the purified and enriched ammonium perrylate solution prepared in Step 2 into an evaporation container, and perform micro-pressure ultrasonic heating for evaporative crystallization. The stirring speed is 180 r / min, the pressure is 0.2 kPa, the ultrasonic power is 4000 W, and the heating temperature is above 95℃. When a large number of crystals appear, stop heating when the specific gravity of the solution reaches 1.12. Stop stirring and turn off the ultrasonic generator when the solution temperature drops below 30℃. Centrifuge the crystals and dry them at 150℃ for 24 h to obtain high-purity ammonium perrylate with a purity ≥4N.
[0026] The purity of the prepared high-purity ammonium perrylate product was tested to be: ammonium perrylate 99.993%, and the contents of other impurities were: copper 0.0006%, arsenic 0.0001%, sodium 0.0001%, zinc 0.001%, and iron 0.0015%.
[0027] Example 4 A method for preparing high-purity ammonium rheniumate, wherein the main components of the rhenium-rich slag are: rhenium 1.26%, copper 5.3%, bismuth 2.1%, arsenic 0.8%, sulfur 33.5%, oxygen 24.9%, and sodium 4.2%; the method includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir until homogeneous. The solid-liquid ratio of rhenium-rich slag to water is 1:5. Add hydrogen peroxide, with the amount of hydrogen peroxide being 1.3 times the theoretical amount. Heat to 90°C while stirring at 150 r / min, and pressurize to 0.8 MPa with air. Leach for 90 min, then filter precisely and allow to stand to obtain the leachate. The filter paper pore size is 2 micrometers. The main components of the leachate are: rhenium 2.47 g / L, acidity 68 g / L, copper 12.3 g / L, bismuth 4.8 g / L, arsenic 1.2 g / L, and sodium 8.3 g / L. Step 2: Inject the leachate prepared in Step 1 into a four-stage anion exchange column. The leachate passes through the four-stage anion exchange column sequentially at a flow rate of 100 mL / min. After passing through the four-stage anion exchange column, the rhenium ions are adsorbed onto the exchange resin, and the OH groups on the resin... - Released into the solution and reacting with H - Ions combine to form H₂O, which is discharged with the adsorption liquid. The adsorption liquid then enters the copper smelting system to recover copper and other valuable metals. When the rhenium content in the adsorption liquid of the fourth-stage anion exchange column is detected to be 0.5 mg / L, it is confirmed that the resin of the first-stage ion exchange column is saturated. Ion exchange is stopped, and the first-stage exchange column is eluented with 10% (w / w) high-grade ammonia at a flow rate of 40 ml / min. During the eluenting process, rhenium ions enter the ammonia water to form ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia water... - The radical ions bind to the resin, and the concentration of rhenium in the ammonium perrylate solution is 18 g / L; Step 3: Inject the purified and enriched ammonium perrylate solution prepared in Step 2 into an evaporation container, and perform micro-pressure ultrasonic heating for evaporative crystallization. The stirring speed is 150 r / min, the pressure is 0.2 kPa, the ultrasonic power is 3000 W, and the heating temperature is above 95℃. When a large number of crystals appear, the heating is stopped when the specific gravity of the solution reaches 1.1. When the solution temperature drops below 30℃, stirring is stopped and the ultrasonic generator is turned off. The crystals are centrifuged and dried at 150℃ for 24 h to obtain high-purity ammonium perrylate with a purity ≥4N.
[0028] The mass percentage content of each major component in the prepared product, as tested, is as follows: ammonium perrylate 99.995%, copper 0.0015%, arsenic 0.0001%, sodium 0.0001%, zinc 0.0001%, and iron 0.0006%.
[0029] Comparative Example 1 (1) A method for preparing and purifying high-purity ammonium perrylate, wherein rhenium-rich slag is subjected to conventional oxidation leaching with a solid-liquid ratio of 1:4, a temperature of 80℃, an oxidant dosage of 1.2 times the theoretical amount, a leaching rate of less than 70%, and a leaching solution containing 1.5 g / L rhenium, 80 g / L acidity, 8.5 g / L copper, and 3.2 g / L bismuth.
[0030] Experiments have shown that the leaching rate of rhenium decreases when pressure oxidation leaching is not performed, and the leaching rates of copper and bismuth also decrease significantly, which has a great impact on the overall recovery rate of rhenium, copper and bismuth.
[0031] Comparative Example 2 (1) A method for preparing and purifying high-purity ammonium rhenium is to perform micro-pressure oxidation leaching of rhenium-rich slag, with a solid-liquid ratio of 1:5, a pressure of 0.8 MPa, a temperature of 90°C, and an oxidant of 1.2 times the theoretical amount of hydrogen peroxide, and a leaching time of 90 min. The rhenium-rich slag leachate is then clarified by precision filtration. The clarified liquid is the rhenium-rich slag leachate that can undergo ion exchange. The leachate composition is: rhenium content 4 g / l, acidity 80 g / l, copper 20 g / l, and arsenic 1.2 g / l.
[0032] (2) Pass the leachate treated in step (1) through a four-stage ion exchange column at a flow rate of 100 ml / min. When the rhenium content in the effluent of the fourth-stage exchange column is detected to be 0.5 mg / L, stop the ion exchange. Use prepared 10% chemically pure ammonia water to analyze the saturated first-stage exchange column. The analyte is the high-rhenium solution with a rhenium content of about 20 g / L.
[0033] (3) The high-rhenium solution analyzed in step (2) is heated and evaporated to concentrate it. The solution temperature is above 95℃, and the specific gravity of the solution reaches 1.35 g / cm³. 3 The heating and evaporation were stopped, and then the temperature was lowered to allow for cooling and crystallization. The cooling was stopped when the solution temperature dropped to 15°C. The liquid-solid mixture was then centrifuged to separate the solid and liquid components, yielding white crystals, i.e., high-purity ammonium perrylate.
[0034] The test results showed that the product contained 99.89% ammonium perlite, 0.0065% copper, 0.0005% arsenic, 0.0003% sodium, 0.007% zinc, and 0.005% iron.
[0035] Comparative Example 3 A method for preparing and purifying ammonium perrylate includes the following steps: (1) The rhenium-rich slag was leached under micro-pressure oxidation with a solid-liquid ratio of 1:3, a temperature of 90℃, and 1.2 times the theoretical amount of hydrogen peroxide as oxidant. The leaching time was 90 min. The rhenium-rich slag leachate was then clarified by precision filtration. The clarified liquid is the rhenium-rich slag leachate that can undergo ion exchange. The leachate composition is: rhenium content 4.85 g / l, acidity 60 g / l, copper 10.9 g / l, and arsenic 0.3 g / l.
[0036] (2) Pass the leachate treated in step (1) through a four-stage ion exchange column at a flow rate of 100 ml / min. When the rhenium content in the effluent of the fourth-stage exchange column is detected to be 0.5 mg / L, stop the ion exchange. Use prepared 10% chemically pure ammonia water to analyze the saturated first-stage exchange column. The analyte is the high-rhenium solution with a rhenium content of about 12 g / L.
[0037] (3) The high-rhenium solution analyzed in step (2) is heated and evaporated. The solution temperature is above 95℃ and the specific gravity of the solution is 1.35 g / cm³. 3 Stop heating and evaporation, and proceed with conventional cooling and crystallization. Stop cooling when the temperature drops to 15°C, and centrifuge the mixture to obtain white crystals, which is ammonium perrylate.
[0038] The prepared ammonium perrylate contained 99.92% rhenium, 0.035% copper, 0.005% arsenic, 0.002% sodium, 0.005% zinc, and 0.007% iron. Calculations showed a rhenium recovery rate of 75%, a copper leaching rate of 80%, and an ammonium perrylate crystallization rate of 60%. The objective of comprehensively recovering and producing high-purity ammonium perrylate was not achieved.
[0039] In the above embodiments, the ion exchange resin filled in the ion exchange column is a weakly basic macroporous anion exchange resin with a tertiary amine functional group, named RCX-5, and the amount of ion exchange resin is 2 / 3 of the volume of the exchange column.
[0040] The above are merely preferred embodiments of the present invention. It should be noted that, for those skilled in the art, other equivalent modifications and improvements can be made based on the technical teachings provided by the present invention, and these should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing high-purity ammonium perrylate, characterized in that: Includes the following steps: Step 1: Add rhenium-rich slag and water to a high-pressure reactor and stir evenly. The solid-liquid ratio of rhenium-rich slag and water is 1:3-5. Add hydrogen peroxide as an oxidant. Heat to 80-90℃ while stirring at a rate of 150-200 r / min. Pressurize to 0.6-1.0 MPa with air and leach for 60-90 minutes. Filter precisely and let stand to obtain the leachate. Step 2: Pass the leachate prepared in Step 1 through a four-stage anion exchange column. When the rhenium content in the solution after adsorption at the fourth stage anion exchange column is detected to be 0.1-0.5 mg / L, confirm that the resin in the first-stage ion exchange column is saturated, stop the ion exchange, and then elute the first-stage exchange column with high-quality ammonia. During the elution process, rhenium ions enter the ammonia to form an ammonium rhenium solution. The eluent is the purified and enriched ammonium rhenium solution. The H₂O in the ammonia... - The radical ions then bind with the resin, purifying the concentrated ammonium perrylate solution to a rhenium concentration of 15-20 g / L. Step 3: Inject the purified and enriched ammonium perryate solution prepared in Step 2 into an evaporation container. Under the action of micro-pressure ultrasound, perform high-temperature thermal crystallization by heating and evaporation. The stirring speed is 150-200 r / min, the pressure is 0.2 kPa, the ultrasonic power is 3000-5000 W, and the heating temperature is above 95℃. When a large number of crystals appear in the solution under these conditions, stop heating when the specific gravity of the solution reaches 1.1-1.
15. Stop stirring and turn off the ultrasonic generator when the solution temperature drops below 30℃. Centrifuge and dry the crystals to obtain high-purity ammonium perryate crystals with a purity ≥4N.
2. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: The main components in the rhenium-rich slag are as follows: rhenium 1-2%, copper 5-8%, bismuth 1-3%, arsenic 0.5-1%, sulfur 30.0-34.2%, oxygen 21-25.8%, and sodium 3-5%.
3. The method for preparing high-purity ammonium perrylate according to claim 2, characterized in that: The main components in the leachate produced in step one are: rhenium 2-5 g / L, acidity 50-80%, copper 15-20 g / L, bismuth 3-7 g / L, arsenic 0.5-1.0 g / L, sodium 10-13 g / L, and sulfur 20-25 g / L.
4. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: The filter paper used in the precision filtration step one has a pore size of 1-5 micrometers.
5. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: In step two, the leachate is sequentially passed through a four-stage anion exchange column at a flow rate of 80-100 mL / min. After passing through the four-stage anion exchange column, the perylene ions are adsorbed by the exchange resin, and the OH groups on the resin are... - Released into the solution and reacting with H - The ions combine to form H2O, which is discharged with the adsorbed liquid. The adsorbed liquid then enters the copper smelting system to recover copper and other valuable metals.
6. The method for preparing high-purity ammonium perrylate according to claim 5, characterized in that: The ion exchange column is filled with a weakly basic macroporous anion exchange resin with a tertiary amine functional group, named RCX-5, and the amount of exchange resin is 2 / 3 of the column volume.
7. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: The amount of hydrogen peroxide used in step one is 1.2-1.5 times the theoretical amount.
8. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: In step two, the superior ammonia water is chemically pure ammonia water with a mass percentage concentration of 5-10%, and the flow rate of the ammonia water is 30-50 ml / min when the saturated anion exchange column is desorbed.
9. The method for preparing high-purity ammonium perrylate according to claim 1, characterized in that: The drying conditions for the crystals in step three are: drying at 150℃ for 24 hours.